AIDing Chromatin and Transcription-Coupled Orchestration of Immunoglobulin Class-Switch Recombination - Vaidyanathan, Bharat; Yen, Wei-Feng; Pucella, Joseph; Chaudhuri, Jayanta (Frontiers in Immunology, 2014)
Secondary diversification of the antibody repertoire upon antigenic challenge, in the form of immunoglobulin heavy chain (IgH) class switch recombination (CSR) endows mature, naïve B cells in peripheral lymphoid organs with a limitless ability to mount an optimal humoral immune response, thus expediting pathogen elimination. CSR replaces the default constant (CH) region exons (Cμ) of IgH with any of the downstream CH exons (Cγ, Cε or Cα), thereby altering effector functions of the antibody molecule. This process depends on, and is orchestrated by, activation-induced deaminase (AID), a DNA cytidine deaminase that acts on single-stranded DNA (ssDNA) exposed during transcription of switch (S) region sequences at the IgH locus. DNA lesions thus generated are processed by components of several general DNA repair pathways to drive CSR. Given that AID can instigate DNA lesions and genomic instability, stringent checks are imposed that constrain and restrict its mutagenic potential. In this review, we will discuss how AID expression, substrate specificity and activity is rigorously enforced at the transcriptional, post-transcriptional, post-translational and epigenetic levels, and how the DNA damage response is choreographed with precision to permit targeted activity while limiting bystander catastrophe.